Innovating through Clusters. (6th November 2014) - D'Alise, Chiara; Giustiniano, Luca; Peruffo, Enzo
This paper focuses on innovation performance and investigates the impact of clusters, or localized networks involving industrial, academic and institutional players, in the pharmaceutical setting; we aim to enrich the line of inquiry into cluster-based innovation by applying a social network analysis (SNA) approach. The cluster concept has been defined in ambiguous ways, corresponding to a large variety of spatial and organizational concrete configurations. By analysing the U.S. pharmaceutical context, we show the structural and nodal network characteristics of the clusters and we shed some light on the "small-world" effects of the structural holes.